Uropodina species from Vietnam (Acari: Mesostigmata) - Kontschán, Jenő; Starý, Josef (Zootaxa, 2011)
Sixteen species of Uropodina were found in samples of soil mites from Vietnam, in the Institute of Soil Biology of the Biology Centre AS CR (Èesk Budìjovice, Czech Republic) and the Soil Zoology Collections of the Hungarian Natural History Museum (Budapest, Hungary). Five of them are known species — Angulobaloghia vietnamensis (Kontschán, 2008), Metagynella vietnamensis Hiramatsu, 1981, Uroobovella similitakensis Hirschmann, 1981, Uroobovella topali Hirschmann, 1981, and Uropoda hirschmanni Hiramatsu, 1977. Eleven species are described as new — Trachytes vietnamensis sp. nov., Dinychus serratus sp. nov., Trichouropoda aspera sp. nov., Uroobovella oviformis sp. nov., Uroobovella multisetosa sp. nov., Paradinychus pilosus sp. nov., Phymatodiscus kuni sp. nov., Uropoda setata sp. nov., Uropoda lichenicola sp. nov., Angulobaloghia scrobia sp. nov. and Depressorotunda (Depressorotunda) alveolata sp. nov. The genus Paradinychus is resurrected and three species are moved into this genus, as P. sumatrensis (Vitzthum, 1921) comb. nov. and P. fistulata (Hiramatsu, 1982) comb. nov. Keys to the species of the genus Paradinychus, to the Asian species of Trachytes and to the Uropoda spiculata species group are given.